Patterns of physical activity and sedentary behavior after bariatric surgery: An observational study - Chapman, N.; Hill, Kylie; Taylor, S.; Hassanali, M.; Straker, Leon; Hamdorf, J. (Elsevier Inc., 2014)
Background - Engaging in low levels of physical activity (PA) and accumulating prolonged periods of sedentary behavior (SB) during daily life have been associated with deleterious health outcomes. The objective of this study was to undertake an analysis of the way in which PA and SB were accumulated after bariatric surgery. Methods - Adults 12 to 18 months after laparoscopic adjustable gastric banding or 6 to 18 months after laparoscopic sleeve gastrectomy wore 2 activity monitors during the waking hours for 7 days. Anthropometric and demographic data were recorded. Results - Data were available on 40 participants (30 females; median ± interquartile range: age 46 ± 16 years, time since surgery 14 ± 8 months, body mass index 36 ± 9 kg/m2). The proportion of waking hours spent in SB, light PA, moderate PA, and vigorous PA was 72% ± 12%, 22% ± 9%, 5% ± 3% and 0% ± 0%, respectively. Half of the time in SB was accumulated in uninterrupted bouts≥30 minutes. Almost all PA was accumulated in bouts<10 minutes in duration. The median daily step count was 9108 ± 4360. The proportion of people who completed an average of≥10,000 steps/d was similar to that reported in Western Australian adults (39% versus 32%; P = .35). Conclusion - Our sample spent>70% of time in SB, half of which was accumulated in uninterrupted bouts≥30 minutes. Very little time was spent in moderate or vigorous PA (5%), and this was accumulated in short bouts (<10 minutes). Healthcare professionals should target not just overall time in SB and PA, but also aim to reduce prolonged periods of SB and increase sustained periods of PA.